El Metatagging y su repercusión en los derechos del consumidor. - Ortiz Guaman, Cristian Fernando (2023)
The main objective of this research project is to analyze, from a legal-doctrinary perspective, the use of metatagging as an unfair practice and its possible infringement of consumers rights in the context of the digital market. In order to achieve this purpose, specific objectives were set out, which include conducting a study of the technical characteristics of metatagging, identifying consumer rights in the digital market through an analysis of international cases, and establishing whether metatagging as an unfair practice affects consumer rights. Using a qualitative approach involving a legal-doctrinary analysis, the technical characteristics of metatagging, its operation in the context of search engines and e-commerce, as well as its relationship with SEO, digital marketing and online advertising were examined. In addition, it delved into the regulation of consumer rights on digital platforms, focusing on the right to information and the protection of personal data. The analysis included a review of how metatagging can influence consumer decisions and how it is legally protected, particularly in the context of Ecuador. A comparison of international regulations related to the use of metatags and their impact on consumer rights was also conducted. International cases were studied that illustrated how the incorrect use of metatags can generate legal conflicts and violate consumer rights. The results of the research revealed that metatagging in the digital marketplace can have a significant impact on consumer rights. Although this technique can be used legitimately to improve the visibility of a website, its nappropriate use can lead to unfair practices that harm the consumer experience and their ability to make informed decisions.